(untitled) (Veterinary Science, 2023)
In order to develop a simulation model that reconciles the different biological-based mathematical algorithms used to calculate mineral requirements in beef cattle, bibliographic theoretical information has been compiled to lay the foundations for it. The model was developed in an Excel environment with the help of Excel macros. Two mineral samples were evaluated, simple mineral salt and protein salt for beef cattle. For validation were employed beef cattle with +/-290 kg body weight maintained on native pasture. Both, the mineral salt as the protein salt showed deficiencies to cover the mineral requirement of macro minerals, mainly phosphorus with a shortfall of 56 % in average. In the case of the trace minerals they were all covered sufficiently and expressed excesses principally in Fe and Mn, both for the mineral salt and for the protein salt. As for the simulations of daily weight gain, the software yielded results in both cases with lower daily weight gains than those obtained in practice, with a difference of 12%